PERILAKU PROSOSIAL (PROSOCIAL BEHAVIOR); Telaah Konseptual Tentang Altruisme (Altruism) Dalam Perspektif Psikologi - Mohamat Hadori (LP2M Universitas Ibrahimy, 2014)
Prosocial Behavior is altruism which includes any act designed to give assistance or to help others. Either the providing assistance of individually or groups, is a proof that have compassion to help anothers. However, the real, it does not mean actually been cleared of the improper behavior of people who abuse the situation for a his benefit of certain individual.